2014
DOI: 10.3109/0284186x.2014.923934
|View full text |Cite
|
Sign up to set email alerts
|

Time-trends on incidence and survival in a nationwide and unselected cohort of patients with skeletal osteosarcoma

Abstract: BackgroundThis study describes time-trends on epidemiology, subtypes and histopathological entities of osteosarcoma (OS) in a nationwide and unselected cohort of OS patients in Norway between 1975 and 2009. Few nationwide studies are published, and we still have particularly limited knowledge regarding patients not included in clinical trials comprising about half of the OS population.MethodHistologically verified skeletal OS for all subgroups were included, resulting in 473 eligible cases from a total of 702 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
131
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(137 citation statements)
references
References 21 publications
5
131
1
Order By: Relevance
“…Though there are many advances in the surgical resection and adjuvant chemotherapy for osteosarcoma in recent years, the prognosis for osteosarcoma patients has not been obviously improved [3]. A study from Norway showed that there was no improvement in the overall survival for osteosarcoma since the 1990s, and the survival rates were still poor for elderly people or patients with metastatic diseases [2]. Previous studies have suggested that patients with poor histological response to chemotherapy or advanced stages usually have worse prognosis [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though there are many advances in the surgical resection and adjuvant chemotherapy for osteosarcoma in recent years, the prognosis for osteosarcoma patients has not been obviously improved [3]. A study from Norway showed that there was no improvement in the overall survival for osteosarcoma since the 1990s, and the survival rates were still poor for elderly people or patients with metastatic diseases [2]. Previous studies have suggested that patients with poor histological response to chemotherapy or advanced stages usually have worse prognosis [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Osteosarcoma is the most common primary malignant bone tumor [1,2]. Though there are many advances in the surgical resection and adjuvant chemotherapy for osteosarcoma in recent years, the prognosis for osteosarcoma patients has not been obviously improved [3].…”
Section: Introductionmentioning
confidence: 99%
“…The malignancy of osteosarcoma is high, with an extremely poor patient prognosis. Osteosarcoma often results in pulmonary metastasis within a number of months, with a 3-5 year survival rate of 5-20% (1). Surgery remains the primary treatment option for patients with osteosarcoma; however, the incidence of relapse for these patients is high (1).…”
Section: Introductionmentioning
confidence: 99%
“…Osteosarcoma often results in pulmonary metastasis within a number of months, with a 3-5 year survival rate of 5-20% (1). Surgery remains the primary treatment option for patients with osteosarcoma; however, the incidence of relapse for these patients is high (1). For patients with advanced stage osteosarcoma who have missed the opportunity for surgical therapy, comprehensive treatments, including radiotherapy, chemotherapy and biological agents, have become the main option for therapy (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the only time period since then during which significant prognostic gains were achieved was from the late 1970s until the early 1980s, when combining multi-agent chemotherapy with surgery revolutionized treatment 2 . Unfortunately, the decades since have witnessed no further improvements of survival in North America 3 or Europe 46 . Nevertheless, there have been numerous advances in the management of osteosarcoma which merit review and discussion.…”
Section: Introductionmentioning
confidence: 99%